JMASM37: Simple Response Surface Methodology Using RSREG (SAS) - Wan Ahmad, Wan Muhamad Amir; Mohd Ibrahim, Mohamad Shafiq; Mokhtar, Kasypi; Aleng, Nor Azlida; A. Rahim, Hanafi; Ali, Zalila (Journal of Modern Applied Statistical Methods Inc, 2016)
Response surface methodology (RSM) can be used when the response variable, y, is influenced by several variables, x’s. When treatments take the form of quantitative values, then the true relationship between response variables and independent variables might be known. Examples are given in SAS.